Unstable angina pectoris prior to ST elevation myocardial infarction in patients treated with primary percutaneous coronary intervention has no influence on prognosis - Kluz, Krystyna; Parenica, Jiri; Kubkova, Lenka; Littnerova, Simona; Tomandl, Josef; Poloczek, Martin; Toman, Ondrej; Tesak, Martin; Cermakova, Zdenka; Gottwaldova, Jana; Manousek, Jan; Pavkova Goldbergova, Monika; et al. (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2015)
BACKGROUND: Pre-infarction unstable angina pectoris (UAP) can be considered ischemic preconditioning. The aim of this study was to compare short and long term outcomes in patients with or without pre-infarction UAP and ST elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI). METHODS: 593 patients with STEMI (388 without and 205 with UAP) were evaluated. Levels of biomarkers (troponin I, BNP, NT-ProBNP, neopterin, endoglin and pentraxin-3) at hospital admission and 24 h after STEMI onset were assessed. Echocardiography was undertaken on the fourth day after MI and after 12 months. The median follow-up was 37 months. RESULTS: We found no significant differences in sex, age or risk factors for atherosclerosis between the UAP and non-UAP group. As the median time from the onset of chest pain to admission was significantly longer in the UAP group (228 min vs 258 min; P=0.009), we used a propensity score to obtain comparable matched groups for use in further analyses. The levels of NT-proBNP were significantly higher on admission and after 24 hours in the UAP group. Left ventricular functions according to invasive and echocardiographic parameters were entirely comparable at hospitalization and after 12 months. No differences were found in severity index of acute heart failure during hospitalization. The incidence of major acute coronary events during follow-up was comparable for the groups. CONCLUSIONS: In patients with STEMI treated with primary PCI, pre-infarction UAP has no beneficial clinical effect during hospitalization or during long-term follow-up.
Keywords: senioři; Stroke; Prognosis; Kaplan-Meier Estimate; Middle Aged; mužské pohlaví; infarkt myokardu; Kaplanův-Meierův odhad; Prospective Studies; Adult; recidiva; pre-infarction angina pectoris; cévní mozková příhoda; Follow-Up Studies; Myocardial Infarction; Peptide Fragments; následné studie; ženské pohlaví; prognóza; Time-to-Treatment; Humans; prospektivní studie; Recurrence; Angina, Unstable; primary PCI; biologické markery; peptidové fragmenty; STEMI; koronární angioplastika; srdeční selhání; lidé středního věku; nestabilní angina pectoris; Natriuretic Peptide, Brain; Percutaneous Coronary Intervention; dospělí; natriuretický peptid typu B; Biomarkers; natriuretic peptides; Female; Aged; čas zasáhnout při rozvinutí nemoci; Heart Failure; lidé; Male